2 n positive periodic solutions to n species non‐autonomous Lotka‐volterra unidirectional food chains with harvesting terms - Li, Yongkun; Zhao, Kaihong (Mathematical Modelling and Analysis, 2010)
By using the Mawhin continuation theorem of coincidence degree theory and some results on inequalities, we establish the existence of 2 n positive periodic solutions for n species non‐autonomous Lotka‐Volterra unidirectional food chains with harvesting terms. Two examples are given to illustrate the effectiveness of our results.First published online: 09 Jun 2011